A Therapeutic Approach To Cancer Gene Therapy - Mehta, Gireesh; Yaduwanshi, Yogesh; Shakyawal, Jitendra; Kabra, Mahaveer; Singh, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2013)
Cancer can be described as a disease where cellular communication has broken down, allowing transformed cells to escape tight regulatory signals and to replicate autonomously and continuously, ultimately invading and interfering with the functions of normal tissues. Gene therapy of cancer has been one of the most exciting and exclusive areas of therapeutic research in the past decade. Critical developments have occurred in gene therapy targeting cancer cells, cancer vasculature, the immune system, and the bone marrow, itself often the target for severe toxicity from therapeutic agents. The therapeutic approach and efforts have been made to evaluate the target impact in both preclinical and early clinical trials. All therapeutic strategies that are being developed in the treatment of cancer ultimately aim to destroy cancerous cells while leaving normal cells unaffected. This can be achieved by expression of tumour suppressor genes, oncolytic viruses, expression of genes that initiate cell death, gene-directed enzyme pro-drug therapy, and immunotherapy. Cancer Gene Therapy is the essential gene and cellular therapy resource for cancer researchers and clinicians.